2016
DOI: 10.18203/issn.2454-5929.ijohns20161848
|View full text |Cite
|
Sign up to set email alerts
|

Tracheo-bronchial foreign bodies: our experience at a tertiary care hospital

Abstract: <p class="abstract"><strong><span lang="EN-US">Background:</span></strong>Tracheo- bronchial foreign bodies have always posed a challenge to the ENT surgeon as they present with varied symptomatology ranging from a simple cough and fever to more grave respiratory distress. It requires a strong suspicion, early diagnosis and timely intervention to reduce the overall morbidity and mortality .This study was undertaken to highlight our experiences in handling cases of tracheo- bronchi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Also Meena et al found cough (83.33%) as most common symptom and Suligavi et al found chronic cough and wheeze as the commonest presenting symptoms. 6,8 In our study 40% had symptoms from 5 days to 2 weeks duration followed by >2 weeks (30%) whereas minimum 10% were in <24 hrs followed by 20% in 1 to 5 days. Because we had taken suspected cases the patients were treated at lower level first then refer to tertiary center so longer duration patients were more.…”
Section: Discussionmentioning
confidence: 43%
See 2 more Smart Citations
“…Also Meena et al found cough (83.33%) as most common symptom and Suligavi et al found chronic cough and wheeze as the commonest presenting symptoms. 6,8 In our study 40% had symptoms from 5 days to 2 weeks duration followed by >2 weeks (30%) whereas minimum 10% were in <24 hrs followed by 20% in 1 to 5 days. Because we had taken suspected cases the patients were treated at lower level first then refer to tertiary center so longer duration patients were more.…”
Section: Discussionmentioning
confidence: 43%
“…Similarly, Mukherjee et al and Suligavi et al found vegetables were the most common FBs and whistles from small plastic toys were the single most common non organic FB whereas Nagaraj et al the most common FB extracted was betel nut in 47% of the cases. [8][9][10] We observed 10% patients with pneumonia, 4% had granuloma and 2% had bronchospasm. Also, Wolach et al found pneumonia (the commonest complication) developed before and after bronchoscopy in 28% of the children.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation